Managing Intellectual Capital to Confront the Challenges of Globalization - Djilali, Benabou; Sarra, Bouguesri; Fayçal, Mokhtari (Richtmann Publishing, 2012)
The world has changed dramatically during the last 20years .and the dawn of a new form of civilization has emerged as thenew millennium begins. In this age of rapid, unexpected, and unpredictable changes with far reaching consequences, the role ofgovernments, citizens, organized groups, nation-states, and societies is changing rapidly as well. Public and private organizations, andmanagement systems, are being transformed by either choice or pressure and necessity of adaptation for survival.This article addressesintellectual capital as a new strategic in the age of globalization. After maximizing production factors such as land, buildings, equipmentinventory and financial resources (the tangible assets) ,companies have discovered that the so –called intangible assets (hidden) assetof knowledge can play a vital role in helping, them obtain a sustainable competitive advantage. To meet the challenges of globalization—negative as well as positive—capacity building is needed in areas of organization, management, governance, and public administrationall over the world. The aim of this research is to investigate the different methods in managing intellectual capital due to the globalizationstatus in different Algerian companies The results indicates that without human capital ( as a part of intellectual capital ) nothing can beaccomplished, and without a well-trained, well-developed, well-appreciated, and well-managed human capital, modern organizations ofgovernment and business cannot meet the challenges of the globalization age .It shows also that there is a lack comprehension ofAlgerian managers concerning how to manage intellectual capital in this new era